'Where Men and Gods Command': the monument, the crypt, and the magic word. Issue 1 (May 2019) - Houlton, Thomas
Abstract : This paper examines the relationships between monumental commemoration and memory, placing Rachel Whiteread's Memorial to the Austrian Jewish Victims of the Shoah (2000) as the physical manifestation of Derrida's archive as a place where memory, power, writing and representation intersect. I consider the context and characteristics of Whiteread's memorial alongside the concept of the crypt, formulated by Derrida in his 'Fors' to Nicolas Abraham and Maria Torok's The Wolf Man's Magic Word (1976). I propose that the archive, formed as it as around the crypt, is a place where death and desire co-habit, and that the Holocaust, the subject of Whiteread's sculpture, is itself an archive that has been constructed around what Maria Torok terms the 'exquisite corpse'. This exquisite corpse of the Holocaust encrypts, even in its own commemoration, the erotics and desires of the 'Nazi father' or 'Hitler in uns ', what Derrida terms 'the tombstone of the illicit'. This paper poses the question that we are, even as we remember the Jewish dead, simultaneously re-encrypting the forgetful, murderous Nazi father, and advocates that we maintain a watchfulness on the threshold of the archive, the monument, the text, in order to resist total resolution, complete meaning, the forgetful re-inscription of acts of atrocity.